2013
DOI: 10.5812/jjm.9601
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Biofilm Formation Among Methicillin Resistance Staphylococcus aureus Isolated From Nasal Carriers

Abstract: Background: Methicillin -resistant staphylococcus aureus (MRSA) is associated with serious infections. Having the ability of biofilmformation decrease their susceptibility to antibiotics. Objectives: The aim of this study was to determine the prevalence of biofilm formation among MRSA isolated from nasal carriers in the Beheshti Teaching Hospital in Kashan, Iran. Materials and Methods: A cross-sectional study was conducted in 810 patients referred to emergency department in Beheshti Hospital in Kashan. Sterili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
4
16
1
Order By: Relevance
“…Ohadian Moghadam et al showed high rates of biofilm production (more than 80%) among S. aureus isolates obtained from bourn wound samples in Tehran, North of Iran (23). In another study from Kashan, all MRSA isolates from nasal carries were able to form biofilms (24). These variations in frequency of biofilm producing staphylococci are documented in other parts of the world, as well.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ohadian Moghadam et al showed high rates of biofilm production (more than 80%) among S. aureus isolates obtained from bourn wound samples in Tehran, North of Iran (23). In another study from Kashan, all MRSA isolates from nasal carries were able to form biofilms (24). These variations in frequency of biofilm producing staphylococci are documented in other parts of the world, as well.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, S. epidermidis biofilm producers revealed higher resistance to ampicillin and tetracycline compared to non-biofilm producing isolates (P < 0.05). In two Iranian studies, similar to our findings, most of the biofilm forming staphylococci isolates had higher antibiotic resistance and multiple drug resistance (MDR) rates (23,24). The same findings have been reported by Sahal et al in Turkey, indicating that majority of strong biofilm forming S. epidermidis strains were β-lactams resistant, and notably 100% of them were MDR (33).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm development could be stopped by removing any of the followings: microbes, slime-exopolysaccharides, and surface (7). Different superficial appendices of organisms are related to the first stage of biofilm formation and attachment to eukaryotic host cells such as flagella, fimbriae, autotransporter proteins, curli, F conjugative pilus, and exopolysaccharide production (8).…”
Section: Introductionmentioning
confidence: 93%
“…2017; 4(2):e46049. 100% of MRSA isolates could form a biofilm (14,15). The findings showed that the number of biofilm isolates from the normal flora were more than other clinical samples, which agrees with some previous studies (16,17).…”
Section: Discussionmentioning
confidence: 99%